MANAGEMENT OF AUDIOVISUAL LEARNING MEDIA AND IMPROVEMENT OF STUDENT LEARNING OUTCOMES BY PPKn TEACHERS AT SMA NEGERI 2 TENGGARONG - Elda Arum Puspita; Alim Salamah; A. Hardoko; M. Jamil (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe: (1) the planning of audiovisual learning media management by Civics Education (PPKn) teachers, (2) the implementation of audiovisual learning media management, (3) the improvement of students’ learning outcomes in the cognitive, affective, and psychomotor domains after the use of audiovisual media, and (4) the obstacles and solutions encountered by teachers in managing audiovisual media. This research employed a qualitative descriptive approach. The subjects were Civics Education teachers and grade XII students at SMA Negeri 2 Tenggarong. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the management of audiovisual media by Civics Education teachers was carried out in a planned and integrated manner with learning objectives. The media used included interactive powerpoint, instructional videos, current news broadcasts, and the quizizz application. The evaluation of learning outcomes showed improvements in the cognitive domain (indicated by differences between pre-test and post-test scores), the affective domain (indicated through attitude observation), and the psychomotor domain (indicated through discussions, group presentations, and students’ products/creations). Obstacles encountered included technical and pedagogical limitations, which were overcome through collaborative strategies and the optimization of technology use. Overall, audiovisual media management has proven to contribute positively to improving students’ learning outcomes in terms of knowledge, attitudes, and skills. This research is expected to serve as a reference for teachers in developing innovative, technology-based learning strategies.